Livability planning in gated community residential scheme: Malaysian socio-religious approach - Ahmad Sarkawi, Azila; Abdullah, Alias (EAROPH, 2015)
“Livability” is a broad term with no precise or universally agreed-upon definition. The concept embraces the “character” and states of place arrangement considering broad human needs and wellbeing material and non-material. Out of these broad human needs and wellbeing, the paper focuses on shelter, known as housing or residential in a planning term. Furthermore, the paper narrow down its discussion to gated community (GC) residential scheme. The discussion revolves around GC guidelines in Malaysia and other related laws and regulations. From its definition, GC in Malaysia is a residential scheme enclosed with walls and fences surrounding the entire residential with restricted access and equipped with common property facilities. This paper aims to study the livability planning of GC through its fourteen physical guidelines embodied in GP022 Gated Community and Guarded Neighbourhood, namely, i. development size, ii. site planning, iii. location of development, iv. road system and hierarchy, v. housing design, vi. construction of wall/fence, vii. access, viii. guard post, ix. landscape and tree planting, x. building height, xi. parking lot, xii. utilities, xiii. provision of social facilities, xiv. naming the neighbourhood. Using content analysis, the study found that elements of livability planning have been embedded in GC spatiality. On social dimension, Strata Management Act 2013 helps to facilitate management and maintenance of GC residential scheme effectively. However, GC has still been labelled as social exclusion and homogeneity and crime fear. For such critic, the paper proposes a spiritual content embodied in religion that everybody must possess to ensure we are becoming beneficial not only to our self but to the society also, inviting good and forbidding bad. By this religious virtue, it could bring down the social problems in community that sometimes failed to be addressed through spatial planning.